2011
DOI: 10.1161/circep.110.958082
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of Catheter Ablation Lesions in Infant Hearts With Cryothermal Versus Radiofrequency Energy

Abstract: Background-Radiofrequency catheter ablation in immature hearts has been associated with marked enlargement of lesions over time, with potential for related late adverse events. It remains unknown whether cryothermal ablation lesions display a similar pattern of growth. Methods and Results-Ablation lesions (nϭ384) were performed in 32 infant miniature swine in right and left atria, ventricles, and atrioventricular (AV) grooves preselected by a randomized factorial design devised to compare radiofrequency and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
(46 reference statements)
4
18
0
4
Order By: Relevance
“…należy unikać dożylnego podawania werapamilu, ponieważ lek ten może być przyczyną ostrej dekompensacji hemodynamicznej [476]. U małych dzieci powikłania ablacji przezcewnikowej wydają się częstsze, a ponadto istnieją obawy o konsekwencje w fazie dalszego wzrostu po wywołaniu uszkodzeń termoablacyjnych lub krwioablacyjnych w mięśniu sercowym [475,[485][486][487]. Idiopatyczny VT i złożone PVC u dzieci zwykle ustępują samoistnie w ciągu miesięcy do lat [471].…”
Section: Definicje I Epidemiologiaunclassified
“…należy unikać dożylnego podawania werapamilu, ponieważ lek ten może być przyczyną ostrej dekompensacji hemodynamicznej [476]. U małych dzieci powikłania ablacji przezcewnikowej wydają się częstsze, a ponadto istnieją obawy o konsekwencje w fazie dalszego wzrostu po wywołaniu uszkodzeń termoablacyjnych lub krwioablacyjnych w mięśniu sercowym [475,[485][486][487]. Idiopatyczny VT i złożone PVC u dzieci zwykle ustępują samoistnie w ciągu miesięcy do lat [471].…”
Section: Definicje I Epidemiologiaunclassified
“…3 These include reversibility during testing, smaller lesion size, minimal effects on coronary arteries without reported stenosis, and minimal endocardial disruption with less thrombus formation. 4 -6,12,15 Many of these features were highlighted in the current study by Khairy et al 1 …”
Section: Cryo Versus Rf?mentioning
confidence: 58%
“…4 When the data were in, they actually demonstrated that there were no differences between the late effects of CRYO and RF on developing myocardium, and both techniques led to longterm lesion growth and invasion of scar tissue into surrounding myocardium. 1 …”
mentioning
confidence: 99%
“…[1][2][3]16,18 However, it is important to note that when applied to immature myocardium, the rate of expansion of cryoablation lesions is similar to RFCA. 19 In addition, cryothermal ablation lesions are associated with minimal endothelial surface disruption and a lesser degree of platelet and the coagulation cascade activation when compared with RFCA. 2,20,21 Preclinical studies have demonstrated a significantly lower incidence of overlying thrombus (30.1% versus 75.8% despite the use of aspirin and heparin), and a lesser thrombus volume with cryothermal ablation compared with RF.…”
Section: Lesion Characteristics Endothelial Integrity and Associatementioning
confidence: 99%